Boosting immunity to treat parasitic infections: Asaia bacteria expressing a protein from Wolbachia determine M1 macrophage activation and killing of Leishmania protozoans. (November 2020) - Varotto-Boccazzi, Ilaria; Epis, Sara; Arnoldi, Irene; Corbett, Yolanda; Gabrieli, Paolo; Paroni, Moira; Nodari, Riccardo; Basilico, Nicoletta; Sacchi, Luciano; Gramiccia, Marina; Gradoni, Luigi; Tranquillo, Vito; et al.
Graphical abstract: Highlights: Leishmaniasis is a model disease to investigate macrophage polarization. Wolbachia bacteria can be considered a source of immune-polarizing molecules. A protein of Wolbachia, delivered through Asaia bacteria, determines macrophages activation and killing of parasites. Abstract: Leishmaniases are severe vector-borne diseases affecting humans and animals, caused by Leishmania protozoans. Over one billion people and millions of dogs live in endemic areas for leishmaniases and are at risk of infection. Immune polarization plays a major role in determining the outcome of Leishmania infections: hosts displaying M1-polarized macrophages are protected, while those biased on the M2 side acquire a chronic infection that could develop into a deadly disease. The identification of the factors involved in M1 polarization is essential for the design of therapeutic and prophylactic interventions, including vaccines. Infection by the filarial nematode Dirofilaria immitis could be one of the factors that interfere with leishmaniasis in dogs. Indeed, filarial nematodes induce a partial skew of the immune response towards M1, likely caused by their bacterial endosymbionts, Wolbachia . Here we have examined the potential of Asaia WSP, a bacterium engineered for the expression of the Wolbachia surface protein (WSP), as an inductor of M1 macrophage activation and Leishmania killing. Macrophages stimulated with Asaia WSP displayed a strong leishmanicidal activity, comparable to that determined by the choice-drug amphotericin B. Additionally, Asaia WSP determined the expression of markers of classical macrophage activation, including M1 cytokines, ROS and NO, and an increase in phagocytosis activity. Asaia not expressing WSP also induced macrophage activation, although at a lower extent compared to Asaia WSP . In summary, the results of the present study confirm the immunostimulating properties of WSP highlighting a potential therapeutic efficacy against Leishmania parasites. Furthermore, Asaia was designed as a delivery system for WSP, thus developing a novel type of immunomodulating agent, worthy of being investigated for immuno-prophylaxis and -therapy of leishmaniases and other diseases that could be subverted by M1 macrophage activation.